Performance comparison of single axis tracking and 40 solar panels for sunny weather - Chua Y.L.; Yong Y.K.; Koh Y.Y. (American Institute of Physics Inc., 2023)
The rapid increment in human population and economy growth had led to the rise of the energy demand globally. With the rapid diminishing fossil fuels based energy sources, renewable energy sources had been introduced due to its unlimited availability especially solar energy which is a sustainable and reliable energy. This research was conducted to study and compare the efficiency of the single axis tracking solar panel with a 40 inclined angle solar panel in sunny weather condition. The results indicated that the output generated by the solar panel was directly affected by the angle which the solar panel facing the sun. In terms of performance the single axis tracking solar panel emerged to be more efficient with greater energy generated. 2017 Author(s).